2013
DOI: 10.1108/13522751311326125
|View full text |Cite
|
Sign up to set email alerts
|

Generation Y females online: insights from brand narratives

Abstract: PurposeThe purpose of this paper is to understand the relationships Generation Y females have with fashion brands online. Specifically, it examines the role of the internet and social networks in these relationships.Design/methodology/approachNarrative interviews were employed to gather data from Generation Y women. Analysis was conducted using inductive thematic analysis.FindingsTwo main themes emerged from the data: the importance of social media and the influence of the internet. Findings suggest social net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 63 publications
7
52
0
Order By: Relevance
“…Bannister et al (2013) and Ruane and Wallace (2013) also revealed that males exhibited less favorable attitudes than women regarding social media marketing communications, which is consistent with the results of this investigation for Generation Z. Hence, organizations should take advantage of the fact that female adolescents also participate in a greater quantity of social media activities and are more probable to have favorable affective attitudes toward SNA (Walter, 2014).…”
Section: Demographic Variables' Effect On Young Consumers' Attitude Csupporting
confidence: 85%
“…Bannister et al (2013) and Ruane and Wallace (2013) also revealed that males exhibited less favorable attitudes than women regarding social media marketing communications, which is consistent with the results of this investigation for Generation Z. Hence, organizations should take advantage of the fact that female adolescents also participate in a greater quantity of social media activities and are more probable to have favorable affective attitudes toward SNA (Walter, 2014).…”
Section: Demographic Variables' Effect On Young Consumers' Attitude Csupporting
confidence: 85%
“…The findings also substantiate that Facebook advertising yields similar cognitive attitudes compared to Internet advertising in developed countries [10,65,70]. Additionally, it can be theorized that the results of this study were similar to the outcomes of other SNS investigations, which have been conducted in developed countries, thus confirming corresponding cognitive attitudes between emerging nations (such as SA) and first world nations [31,38,39,50,66]. Bolton et al [8] hypothesized that globalization could result in a rise of homogeneousness owing to the Generation Y cohort's SNS usage, but the veracity of this postulation was in doubt because of the relatively poor information technology access, resources and infrastructure that is evident in emerging countries such as SA.…”
Section: Theoretical Implicationssupporting
confidence: 79%
“…Bolton et al [8] hypothesized that globalization could result in a rise of homogeneousness owing to the Generation Y cohort's SNS usage, but the veracity of this postulation was in doubt because of the relatively poor information technology access, resources and infrastructure that is evident in emerging countries such as SA. Several of the aforementioned inquiries that were implemented in the US and Europe similarly examined Generation Y [31,38,50], thereby demonstrating that South African Generation Y cohort members have similar cognitive attitudes to their international counterparts, which confirms Bolton et al's [8] supposition to be accurate. Thus, this study has made significant additions to advance cohort, attitudinal and SNA research in a developing country.…”
Section: Theoretical Implicationssupporting
confidence: 55%
See 1 more Smart Citation
“…As a result, companies have the opportunity to change and promote innovation, gathering information from social networking and virtual communities and creating value for customers (Dahl et al, 2011;Mount and Martinez, 2014;Moncrief et al, 2015;Palacios-Marqués, 2015); 2. Bearing in mind that there is a young generation which is digital born and very social-networking-active, managers are aware that the use of social media is vital to communicate with the younger consumers (Bolton et al, 2013;Ruane and Wallace, 2013). Finally, form the study literature review, it is important to underline that the adoption, use and implications of social networking tools depend on contingent factors that characterise the firm context (Jiang et al, 2014).…”
Section: Social Media As a Challenge For Managementmentioning
confidence: 99%